Key concepts in educational assessment - Isaacs, T Tina Issacs; Isaacs, Tina. (London: SAGE, 2013)
Key Concepts in Educational Assessment provides expert definitions and interpretations of common terms within the policy and practice of educational assessment. Concepts such as validity, assessment for learning, measurement, comparability and differentiation are discussed, and there is broad coverage of UK and international terminology. Drawing on the considerable expertise of the authors, the entries provide clear definitions, accounts of the key issue, authoritative and reliable information and suggestions for further reading
Includes bibliographical references and index.
Keywords: Educational evaluation